(untitled) (The Peerian Journal, 2024)
The article is dedicated to analyzing public-private partnerships in ensuring public safety in the United States. It examines the evolution of citizen participation in public safety in the United States, with a focus on legislative foundations and modern challenges. The author analyzes the historical development of volunteer initiatives, from the colonial period to modern programs aimed at supporting the activities of federal and local law enforcement agencies. Special attention is given to the legal framework regulating volunteer activities and its significance for effective crime prevention and strengthening public order. The author explores various approaches to involving citizens in law enforcement activities, assessing their effectiveness within the context of the decentralized governance system in the United States. The article also investigates the mechanisms of interaction between government structures and civil society, emphasizing the importance of trust-based relationships and their role in enhancing the effectiveness of public safety programs.